Sub-fossil diatoms from the Saloum Estuary, Senegal, West Africa: Floristic inventory and paleo-productivity evolution along the Ndangonkha core. (March 2023) - Gueye, Adama; Fofana, Cheikh Abdoul Kader; Badiane, Insa; Carre, Matthieu; Youm, Cheikh Ibrahima; Sow, El Hadji
Abstract: As part of our program to reconstruct the estuaries and lagoons history in Senegal and the diatom microflora inventory in Sene-Gambia, a 400 cm long core was taken at Ndangonkha in the Saloum Estuary, near Foundiougne. The dating obtained showed that sedimentation began during the Nouakchottian age, around 6000 years BP, with an average rate of sedimentation higher at the base than at the top where the high hydrodynamics of the environment would have caused sediment reworking. The comparative analysis of the lithology and the microflora showed a perfect correlation between the lutite fraction, the absolute abundance of diatoms and their specific richness. The study involved an inventory of 110 species and varieties belonging to 62 genera. The most represented genera being Nitzschia (10 species) and Cyclotella and Diploneis (5 species each). Five species are cited for the first time in Sene-Gambia and 61 species are also reported from Ndangane Babou. The microflora is dominated by euryhaline forms headed by Cyclotella striata. This dominance could be linked to the frequent variations in salinity between the rainy and dry seasons, while the abundance of marine species could be related to the dominant influence of marine waters. The rare freshwater species encountered could be brought by wind, insects or birds. The analysis of the microfloristic and lithological data showed that the primary paleo-productivity and the specific richness are weak at the base but showed an increase upwards. They are high in zone A, maximum in zone C whereas in zone D they are decreasing before disappearing in the last 10 cm, in relation to the hydrodynamics of the environment. Highlights: At Ndangonkha (Saloum Estuary-Senegal), the sedimentation began around 6000 years BP. 110 species and varieties of diatoms and 62 genera have been inventoried along 400 cm core. The microflora is dominated by euryhaline forms headed by Cyclotella striata . The absolute abundance and the richness of diatoms move in the same direction as the lutite fraction. They depends on the hydrodynamics of the environment.